1978
DOI: 10.1007/bf00286953
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant chromosome as a result of pericentric inversion of X chromosome

Abstract: A structural X chromosome abnormality was found in the karyotype of a tall patient with gonadal dysgenesis and with no extragenital anomalies. Based on her mother's karyotype, which showed a pericentric inversion of the X chromosome: 46,X,inv(X)(p22q24), as well as from G and R banding, we concluded that the abnormal X chromosome of our patient was a recombinant chromosome that had originated as a result of one crossing over in the inversion loop during gametogenesis in her mother. The recombinant X chromosome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…X breakpoints and gonadal development in 31 carriers of balanced X inversions; literature in the Appendix, numbers[89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105] …”
mentioning
confidence: 99%
“…X breakpoints and gonadal development in 31 carriers of balanced X inversions; literature in the Appendix, numbers[89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105] …”
mentioning
confidence: 99%
“…The search for the critical region on the long-arm of the X chromosome that causes POF is still ongoing. Recombinant X chromosomes with Xp duplication and Xq deletion in POF are rare and have been reported in only four cases to date [1][2][3][4] . The youngest was 18 years old.…”
mentioning
confidence: 99%
“…Two fertile cases with pericentric inversions [NikoliS and StoleviC, 1978;Soler et al, 19781 involving Xq24 and Xq22 have been reported. Interstitial deletions of Xq within the critical region are also not inevitably associated with gonadal dysfunction since two such patients were reported to have viable offspring [de la Chapelle et al, 1975;Tabor et al, 19831.…”
Section: Discussionmentioning
confidence: 95%